Liderança dos enfermeiros que atuam em um município de tríplice fronteira do sul do Brasil, frente à crise sanitária de COVID-19 - Silva, Gabriela Kauana da (2023)
Leadership is an essential competence for nurses and must be worked on in their daily routine. There are many challenges in exercising leadership, such as directing behavior and planning actions in order to achieve objectives, supervising and taking legal responsibility for the activities of the nursing team, interpersonal relationships, vision of the future and problem-solving. Working in Primary Health Care in a municipality located in a triple international border region brings even more challenges, such as the language barrier, coworkers with other cultures, and even linked to the international health crisis of the COVID-19 pandemic, in which flows and protocols presented constant changes, great demand for vaccination, in addition to the fear itself, and uncertainties that the new disease brought. It can be said that it is through the nurse's exercise of leadership that synchronization of teamwork, quality care and reduction of nursing errors are achieved, generating better results for the patient. Therefore, the purpose of this research was to evaluate the leadership practices voiced by Primary Health Care nurses in a municipality on the triple border in southern Brazil, in order to deal with the health crisis caused by the COVID-19 pandemic. This is an exploratory, descriptive study with a quantitative and qualitative approach, using the Leadership Practices Inventory instrument and the This is an exploratory, descriptive study with a quantitative and qualitative approach, using the Leadership Practices Inventory instrument and the Bardin's content analysis method. Data was collected from May to July 2023. After collection, the quantitative data was entered into Excel® spreadsheets, composing an electronic database. This database was transferred to the Jamovi program, performing descriptive and inferential statistics using the Mann-Whitney test and Spearman's correlation test. The qualitative data was transcribed in full and after in-depth reading, the recording units were identified. The data form this research demonstrated that the five practices of exemplary leadership were practiced moderately by the nurses and the time working in PHC, age, residence time in Foz do Iguaçu and taking leadership courses showed positive correlations (p <0.0001) with leadership practices. As for the qualitative data, the analysis showed the difficulties encountered by nurses in terms of leadership, such as the lack of efficient communication with management and the lack of protocols for the care of foreigners. Leadership is an important attribute for nurses in Primary Health Care, especially in times of crisis, as the team always look at the behavior of its leader, due to the constant changes in flows and routines. These challenges increase for nurses when working in a region as peculiar as the triple border.